Increasing Thematic Learning Outcomes Through Powerpoint Media In Class Iv Students Of Elementary School 0804 Botung Academic Year 2020/2021 - Bintang Marito Nasution (Indonesian Journal of Basic Education, 2021)
This research is an effort to improve the learning outcomes of fourth grade students of SD Negeri 0804 Botung in thematic learning. One of the causes of the low value of thematic learning at SD Negeri 0804 Botung is the lack of use of media in learning. In learning the teacher only uses books as a medium of learning. Teachers do not package and integrate with other learning media. So that students do not understand the material presented by the teacher. Smart educators must be good at choosing learning media so that students can be motivated to take part in learning activities. The method used is Classroom Action Research (CAR). The results of the research in the pre-cycle showed that students who completed were 7 students in a percentage of 35%. In the first cycle of students who completed as many as 12 students in percent of 60%. While in the second cycle of students who completed as many as 20 students in percent of 100%. This shows that the use of Powerpoint media can improve thematic learning outcomes in grade IV Semester I students of SD Negeri 0804 Botung in the 2020/2021 academic year.